Impact of metallurgical industries on water - Matsie, Simon Sello (Vaal University of Technology, 2012)
The increase in industrial activities has contributed towards an increase in environmental pollution problems. Many ecosystems have deteriorated as a result of an accumulation of pollutants including heavy metals contained in effluents discharged from various industrial processes. Legislative standards require that pollutant levels be controlled to fall within set limits. The World Health Organisation (WHO) states that the following metals: aluminium, chromium, manganese, iron, cobalt, nickel, copper, cadmium, mercury and lead are a concern. The research has focussed on the removal of heavy metals from industrial waste water. This was achieved by investigating, characterising and quantifying pollutants within a metallurgical industry environment resulting from applied operations technology and then looking into abatement measures that can be put in place.The study was done and conclusions are discussed below. Analysis of samples indicated the presence of heavy metals with varying concentrations at different sampling points. D1 borehole is found to have higher chromium levels because ferrochrome was once stored in that catchment area. The dam and road bridge sites manganese content is higher due to suspended particulates settling on the ground and being washed down by water streams . Raw materials from mines contain heavy metals which are transferred to water systems during handling. In this research the toxic metal ion biosorption on an inexpensive and efficient biosorbent from agricultural waste materials has been investigated as replacement strategy for existing conventional systems. The study was conducted by using eucalyptus leaves powder for sequestering heavy metal ions from waste water. The metal uptake from an aqueous solution is facilitated by functional groups in the ligno-cellulosic material Many solids are capable of adsorbing ions and molecules from solutions . The removal of heavy metals from aqueous solution using eucalyptus leaves has been investigated under different experimental conditions viz. initial metal concentration and adsorbent mass. Results obtained indicated a decrease in metal concentration due to biosorption of a known elemental concentration per known volume by a known mass of sorbent over a specific time. Sorption is found to be dependent upon contact time, initial concentration, sorbent dose of small quantities of wastewaters containing heavy metals. In the event of high levels of heavy metal being experienced, ground eucalyptus leaves can be used for heavy metal recovery from wastewater. A procedure covering the sorbent mass required per average specific pollutant concentration over a specific time frame can be compiled to optimise sorption. The advantage of biosorption compared to conventional treatment methods are low cost, high efficiency, minimisation of chemical and biological sludge as well as the regeneration of biosorbents and a possibility of metal recovery.
M. Tech. (Department of Chemistry, Faculty of Applied and Computer Sciences), Vaal University of Technology.
Keywords: Removal of heavy metals; Environmental pollution; Metallurgical industries environment; Pollutants; Industry waste water; Air pollution; Water pollution; Dissertations, Academic -- South Africa.; Environmental chemistry.; Factory and trade waste -- Purification.; Pollutants.; Environmental health -- South Africa.